2018
DOI: 10.1101/498337
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Nucleus accumbens neurochemistry in human anxiety: A 7 T1H-MRS study

Abstract: Individual differences in anxiety provide a differential predisposition to develop neuropsychiatric disorders. The neurochemical underpinnings of anxiety remain elusive, particularly in deep structures, such as the nucleus accumbens (NAc) whose involvement in anxiety is being increasingly recognized.We examined the associations between the neurochemical profile of human NAc metabolites involved in neural excitation and inhibition and inter-individual variation in temperamental and situational anxiety. Twenty-s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 79 publications
1
9
0
Order By: Relevance
“…Therefore, it may possible that psychological stress, as for instance being in the scanner, serves as a confounding variable, which may affect GABA concentrations differentially in healthy controls and T2D patients. However, recent studies showed that stress decreases GABA concentrations in the prefrontal cortex (Strasser et al, 2019;Hasler, van der Veen, Grillon, Drevets, & Shen, 2010; but see also Houtepen et al, 2017). Therefore, it seems unlikely that our findings are due to processes related to stress.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, it may possible that psychological stress, as for instance being in the scanner, serves as a confounding variable, which may affect GABA concentrations differentially in healthy controls and T2D patients. However, recent studies showed that stress decreases GABA concentrations in the prefrontal cortex (Strasser et al, 2019;Hasler, van der Veen, Grillon, Drevets, & Shen, 2010; but see also Houtepen et al, 2017). Therefore, it seems unlikely that our findings are due to processes related to stress.…”
Section: Discussionmentioning
confidence: 69%
“…In support for this hypothesis, high anxiety in Wistar rats is not only associated with decreased mitochondrial respiratory capacity in the nucleus accumbens, as indicated above, but also with increased capacity in the prefrontal cortex [35], and no changes in the basolateral amygdala [36] or in the ventral tegmental area [38]. The sensitivity of the nucleus accumbens to show anxiety-related differences in brain energy metabolites has also been also confirmed with 1 H-NMR spectroscopy approaches in mice [39] and humans [40].…”
Section: Findings On Measurements Of Brain Energy Metabolismmentioning
confidence: 71%
“…Chronic stress promotes anxiety [125] as well as oxidative stress damage [126]. In addition, stress increases brain glutamate levels and shifts the excitatory/inhibitory balance towards increased excitation [40,127,128].…”
Section: Concluding Remarks and Future Directionsmentioning
confidence: 99%
“…Importantly, in our study, we also found that NAc taurine levels were the only ones from the measured metabolites that negatively correlated with passive coping responses in the forced swim test, reinforcing the link between levels of this amino acid and energetically-costly coping responses to adversity. In a recent 7T 1 H-MRS in humans, we have recently found a negative correlation between trait anxiety and NAc taurine content (64). Given the high link between trait anxiety and vulnerability to depression (14, 19), our results support the interest in investigating the causal link between NAc taurine and its potential antidepressant actions.…”
Section: Discussionmentioning
confidence: 98%